The Influence of Electronic Word of Mouth and Brand Image on the Interest in Buying Citilink Passenger Tickets at Juanda International Airport - Safitri Dwi Oktafia; Sri Sutarwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this digital era, customer assessment of airlines can be carried out through social media such as Instagram, Twitter and Facebook. This study aims to determine the effect of electronic word of mouth (e-WOM) and brand image on the intention to buy passenger tickets. This study uses quantitative methods and data collection techniques through questionnaires. The population in this study are passengers. The sample is 100 people. Sampling using nonprobability sampling with purposive sampling technique. In conclusion, the results show that electronic word of mouth and brand image have a significant effect on the purchase intention of Citilink passengers at Juanda International Airport. This is evidenced by the results of the bound F test of 31.154 > 3.09 at a significant 0,00<0,05